Indigenous Voices Charting a Course Beyond the Bicentennial: Eba gwedji jik-sow-dul-din-e wedji gizi nan-ul-dool-tehigw (Let’s try to listen to each other so that we can get to know each other) - Dana-Sacco, Gail (Maine Policy Review, 2020)
The Indigenous peoples of this area, now known as the state of Maine, hold a cultural framework embedded in our languages that reflects a sophisticated understanding of our intimate and complex connections with all people and with the environment in which we live. Our collective identity as Indigenous people resides here and provides a firm foundation for strong healthy communities. Author Gail Dana-Sacco explores the history of Maine’s Indigenous peoples and their interactions with the state of Maine over its 200-year history.